Growth and Spread of the Argentine Black and White Tegu in Florida - Rebecca G. Harvey; Justin Dalaba; Jenny Ketterlin; Art Roybal; Daniel Quinn; Frank J. Mazzotti (EDIS, 2021)
The Argentine black and white tegu is one of the largest lizard species in the Western Hemisphere, growing up to four feet long. The tegu’s broad habitat use and omnivorous diet create the potential for severe ecological impacts in areas outside its native habitat. This publication presents updated information about efforts to understand and manage the problem of invasive tegus in the state of Florida. It presents the implications of continued expansion of their range.